Extensive regulation of the non-coding transcriptome by hypoxia: role of HIF in releasing paused RNApol2 - Choudhry, H; Schödel, J; Oikonomopoulos, S; Camps, C; Grampp, S; Harris, AL; Ratcliffe, PJ; Ragoussis, J; Mole, DR (EMBO Press, 2013)
Hypoxia is central to both ischaemic and neoplastic diseases. However, the non-coding transcriptional response to hypoxia is largely uncharacterized. We undertook integrated genomic analyses of both non-coding and coding transcripts using massively parallel sequencing and interfaced this data with pan-genomic analyses of hypoxia-inducible factor (HIF) and RNApol2 binding in hypoxic cells. These analyses revealed that all classes of RNA are profoundly regulated by hypoxia and implicated HIF as a major direct regulator of both the non-coding and coding transcriptome, acting predominantly through release of pre-bound promoter-paused RNApol2. These findings indicate that the transcriptional response to hypoxia is substantially more extensive than previously considered.